Tumaco: Collaboration of Mobile Devices in Hypermedia-based In-Vehicle Infotainment Systems - Grévisse, Christian (2015)
In-Vehicle Infotainment systems nowadays are largely limited to one-to-one relationships with the drivers’ mobile phone. In this paper, we propose Tumaco, a SOA-based IVI system, which enables the seamless integration of all devices of all passengers. Collaborative services can be executed within a cross-platform ecosystem through the use of semantic hypermedia. In addition, passengers may customize their own user experience in order to reduce mental workload. Our prototypical implementation showed the benefits of opening the user experience to all passengers on a car. Finally, we present a framework that enables developers to provide their own services within our ecosystem.